(untitled) (Experimental biology, 2015)
The methods of the audiovisual activating of organs and systems of studying are examined at the level of wave biological processes. The method of activating of centers of perceptible perception of sound and color allows to synchronize the processes of development of sense-organs and speech, accelerating development of student the same.